Integrating inside and outside innovators: A sociotechnical systems perspective - Neyer, Anne-Katrin; Möslein, Kathrin; Bullinger-Hoffmann, Angelika (R & D Management, 2009)
Innovation literature stresses the importance of opening the innovation process to internal and external innovators. The question of what determines the integration of these types of innovators in the innovation process remains open. We use a sociotechnical systems perspective to address a number of challenges with respect to this matter: an organization deploying different innovation practices to open the innovation process might not be aware which types of innovators are de facto integrated in its innovation process. Alternatively, an organization targeting the integration of a particular type of innovator might not use the suitable innovation practices to integrate the knowledge of this type of innovator. To address these challenges, our comparative case-study analysis in 15 medium-sized firms derives a theoretical framework proposing that a combined analysis of innovation practices and underlying social interactions is needed to decide about the integration of a particular type of innovator in the innovation process. Being aware of these interrelations will allow organizations to act more consciously when opening their innovation processes. © 2009 Blackwell Publishing Lt
WiSo-Import:2015-03-26:2023
Keywords: Special issue on Open Innovation by Chesbrough; O.; H.; Gassmann; Enkel; E.